The healthcare costs of physical inactivity among adults in Estonia - Johann Saavaste; Aleksei Baburin; Mall Leinsalu; Rainer Reile (BMC Public Health)
Abstract Background Physical inactivity is a known risk factor for several non-communicable diseases that represent considerable disease burden and implications for healthcare budgets. This cost-of-illness study analyses the impact of adult physical inactivity to healthcare costs in Estonia. Methods Prevalence-based population attributable fraction (PAF) method was used to assess the direct healthcare costs of treatment, medication use and costs of sickness and care benefits of 15 health conditions attributable to physical inactivity. The analysis used various context-specific data sources using both individual level and aggregated data and was carried out from healthcare perspective for the year 2021. The robustness of annual cost estimates was evaluated using both one-way sensitivity analyses and a scenario analysis. Results In 2021, 73.7% (95% CI 72.2–75.1%) of Estonian population aged ≥ 18 years were physically inactive. The annual healthcare costs associated with physical inactivity were €24.64 million of which 92.4% (€22.77 million) consisted of treatment costs. The highest treatment costs were related to cardiovascular diseases (€7.82 million) and type II diabetes (€6.79 million). Depending on data and assumptions tested, the healthcare costs of physical inactivity could reach €47.4 million according to sensitivity analysis. Conclusion Although the healthcare costs attributable to physical inactivity accounted less than 2% of national health insurance expenses, the physical inactivity lays on the etiological pathway to many noncommunicable diseases and remains an increasing public health challenge.